Leadership, values and gender : a study of Icelandic head teachers - Larusdottir, Steinunn Helga (Institute of Education, University of London, 2008)
This is a case study about the values of male and female head teachers in Icelandic schools in the context of an era of educational change. The study's methodology is located within the interpretive framework and informed by the perspectives of social constructivisin and feminism. In addition, the theoretical framework is based on theories related to values in leadership, which, in combination with research on leadership and gender, provide the focus for this study. Data collection mainly involved interviews but also documentary analysis. The purpose of the study was to shed light on the interplay between values, gender, and leadership behaviour. This was done by seeking answers to questions about the impact of headteachers' values on their actions, in particular when facing value related dilemmas. Further questions were asked about the influence of gender on headteachers' values and actions. The study provides information about the impact of recent changes in the envirom-nent of Icelandic schools, on the role of headteachers.I t moreover highlights the genderedn ature of these changesa nd how they may impact differently upon men and women head teachers. The study shows that despite similar values, the position of men and women headteachersis unequal. Several influencing factors were found to contribute to this unequal positioning of men and women, including different careers, discriminatory behaviour towards women, and new competencies, such as computer literacy where more men than women are proficient. The thesis makes a theoretical contribution through conceptualizing and developing a framework for examining the interplay between the concepts of leadership, values and gender and by showing how values, gender and gendered educational discourses, may impact upon leadership actions. It is moreoever a contribution to the existing research on education in general and on leadership, values and gender, specifically.